PENDAMPINGAN TEKNIK ANALISIS PENDAPATAN USAHA TERNAK BABI DI DESA SULI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Matatula, Michel Johan; Sarfan, Rini (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2024)
The potential for developing a pig farming business is largely determined by the increase in the farmer's income, so calculating production costs and the income received by the farmer is important to determine the economic feasibility of the business. The pig farming business in Suli Village has been developed intensively by farmers in the hope that the results of their production will further increase their family income. The problem faced by pig farmers in Suli Village related to income is the difficulty in determining the basic price of pigs to be sold because they do not have records of expenses (production costs) during the production process. Thus, breeders need to be trained to regularly record all expenditure values so that they can market their products at acceptable prices. The activity stages begin with observations and approaches to obtain information about business conditions and the needs of pig farmers. The next stage is counseling, discussion and direct practice on how to record production costs to be used in determining selling prices. As a result of this activity, farmers can calculate production costs, receipts and income from their pig farming business.